PERLINDUNGAN TERHADAP ANAK MELALUI PENDEKATAN RESTORATIF JUSTICE BAGI KORBAN PERKAWINAN ANAK BAWAH UMUR DALAM PERSPEKTIF HUKUM PIDANA DI KABUPATEN SIGI - Julianti Paseru, Ika Sari (Universitas Tadulako, 2024)
The phenomenon of underage child marriage is seen very often nowadays. The problem of this research is the protection of children through a restorative justice approach to criminal acts of underage marriage in Sigi Regency, and the regulation of criminal law for perpetrators of underage marriage in the context of fulfilling children's rights in Sigi Regency. using empirical research methods. Based on the research results, the protection of children through a restorative justice approach for victims of criminal acts of underage marriage aims to restore the situation to the way it was before the violation of marriage provisions occurred by carrying out or applying the provisions of religious values ​​in restorative justice and customary law values ​​in restorative justice. justice because violations of child marriage meet the material and formal requirements for restorative justice to be carried out, apart from that, it is carried out by determining a dispensation for child marriage and child marriage is a violation of the provisions on child protection, sexual violence, the Criminal Code and the Marriage Law relating to guarantees of children's rights, there is no enforcement The law against child marriage in the Sigi Regency area is due to several factors taken into consideration, such as if the law enforcement process results in the child or both parents being processed by criminal justice, it will result in the continuation of the child marriage, so it is discretionary and restorative justice is carried out. In cases of child marriage, the headman will be subject to administrative sanctions from the KUA Office or the Sigi Regency Ministry of Religion.